Google Classroom-Based Blended Learning Learning Tool to Improve Scientific Literacy and Critical Thinking Skills of Students in Chemical Bonding Material - Pera Marita; Adlim; Andi Ulfa Tenri; Muhammad Syukri; Habibati; Zulfadli; M Hasan; Ibnu Khaldun (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to obtain high-quality google classroom-based Blended learning learning tools to improve scientific literacy and critical thinking skills of class X students of Public Senior High School 3 Langsa. and find out the differences in the increase in scientific literacy of class X students of Public Senior High School 3 Langsa after the application of Google Classroom-based Blended Learning learning tools. This research consisted of two stages. The first stage is R & D. Based on the type of research, this research is research and development (R & D). The development in this study follows the development procedure developed by Borg & Gall. The population in this study were all students of class X at Public Senior High School 3 Langsa City which consisted of 6 MIA classes, namely 180 students. Meanwhile, which were selected using the purposive sampling method. The results of the study show that Google Classroom-based Blended Learning learning tools have been developed to improve scientific literacy and critical thinking skills of class X students of Public Senior High School 3 Langsa. These tools are in the form of valid and effective lesson plans and worksheets to improve students' scientific literacy and critical thinking.